Pens and bayonets letters from the front by soldiers of Yorke Peninsula during the Great War - Longo, Don (Wakefield Press, 2018)
This book gives voice to the young Australia soldiers who volunteered to fight for our freedom in the Great War. Letters written during quiet periods give us an insight and sometimes graphic account of the day-to-day encounters during the Gallipoli campaign and various offensives on the Western Front and Palestine.